2011
DOI: 10.1136/sextrans-2011-050109.51
|View full text |Cite
|
Sign up to set email alerts
|

O1-S09.03 Main results and impact analysis of annual Chlamydia screening in a large register-based programme in the Netherlands

Abstract: S09.02 figure 1 suggests local elimination is likely to occur earlier in Bellary (median: 2023) than in Mysore (2028) and Belgaum (2030), with the required intervention duration being 11e35 years. The discounted cost of achieving local elimination in each of the settings is estimated to be $8-11 000 000 with 5000e11 000 HIV infections averted up to 2050.Abstract O1-S09.02 Figure 1 Posterior distribution of the year when HIV indicates in FSWs and clients goes below 1 infection per 1000 FSWs and clients.Conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Cohen et al found that overall chlamydia positivity decreased in intervention schools and was lower after five screening rounds (6.7%, 77/1150) than in control schools tested for the first time (9.3%, 247/2653, risk ratio 0.72 (95% CI 0.56, 0.92) Results presented separately by sex showed that the reduction in intervention schools was seen in boys (5.9%, 34/575 in the first round in year 1 and 3.2%, 19/588 in year 3, p=0.028) but not girls (12.1%, 62/513 in the first round in year 1 and 10.3%, 58/562 in year 3, p=0.359). The incidence also decreased in boys (4.5% from round 1-2 and 3.2% from round 4-5) but not girls (7.2% and 11.4%, respectively) [175]. Van den Broek et al found no change in chlamydia positivity in intervention clusters after three screening rounds (4.1%) compared with control clusters at the first screening round (4.3%, risk ratio 0.96, 95% CI 0.84, 1.09).…”
Section: Study Populations and Intervention Uptakementioning
confidence: 95%
See 4 more Smart Citations
“…Cohen et al found that overall chlamydia positivity decreased in intervention schools and was lower after five screening rounds (6.7%, 77/1150) than in control schools tested for the first time (9.3%, 247/2653, risk ratio 0.72 (95% CI 0.56, 0.92) Results presented separately by sex showed that the reduction in intervention schools was seen in boys (5.9%, 34/575 in the first round in year 1 and 3.2%, 19/588 in year 3, p=0.028) but not girls (12.1%, 62/513 in the first round in year 1 and 10.3%, 58/562 in year 3, p=0.359). The incidence also decreased in boys (4.5% from round 1-2 and 3.2% from round 4-5) but not girls (7.2% and 11.4%, respectively) [175]. Van den Broek et al found no change in chlamydia positivity in intervention clusters after three screening rounds (4.1%) compared with control clusters at the first screening round (4.3%, risk ratio 0.96, 95% CI 0.84, 1.09).…”
Section: Study Populations and Intervention Uptakementioning
confidence: 95%
“…Second, the order of roll-out of the screening invitations was randomised and third, analysis of the primary outcome, adjusting for baseline differences, was the same as the crude analysis. In the trial by Cohen et al the risk of selection bias was higher [175]. Chlamydia screening was introduced first in three schools (intervention group) and then, after two years, into a further five schools (control group).…”
Section: Risk Of Bias In Included Trialsmentioning
confidence: 99%
See 3 more Smart Citations